Producing Dietary Fibers from Sugarcane Bagasse Using Various Chemical Treatments and Evaluation of their Physicochemical, Structural, and Functional Properties - Mohamed Allam, Gelan Sabry; Abd El-Aal, Adel Mohamed; Sayed Morsi, Mohamed Khairy; Abd El-Salam, Ekarm Abd El-Salam (Applied Science and Engineering Progress, 2024)
Sugarcane bagasse (SB) like other lignocellulosic materials contains high levels of insoluble dietary fibers (IDF) that can be extracted using various treatments. Moreover, the extracted IDF properties were found to be dependent on the implemented treatment. Thus, this study set out to evaluate the impact of five treatments (NaOH, NaOH+H2O2, NaOH+H2SO4, PAA (peracetic acid) and NaOH+PAA) and the subsequent bleaching treatment on the physicochemical, structural, and functional properties of SB fiber. In addition, the effect of particle size reduction on the physicochemical and functional properties was investigated. Lignin content, holocellulose content, XRD, FT-IR, and whiteness index were used to characterize the extracted fibers and to evaluate their structural modifications. The experiments confirmed that NaOH+PAA treatment extracted fibers that had the lowest lignin content (1.65%) and highest holocellulose content (93.07%) and exhibited the highest whiteness index (83.37). The high crystallinity index of NaOH+PAA extracted fibers in addition to the disappearance of spectral bands at 1512, 1595, 1620 and 1730 cm–1 of NaOH+PAA FT-IR spectrum confirms the preceding outcomes. The water holding capacity (WHC) and oil binding capacity (OBC) of NaOH+PAA extracted fiber and other extracted fibers were improved as a result of bleaching treatment. Reducing the particle size of treated bleached samples to > 500 μm significantly decreased their WHC and OBC whereas increased their α-amylase inhibitory activity. The obtained results indicate that NaOH+PAA is a promising method for the extraction of fibers from SB under moderate conditions.